Hereditary pseudocholinesterase deficiency in a 4-year-old girl: a case report - Julia Schulze-Berge; Lukas Pillong; Birgit Busse; Wolfram Henn; Nasenien Nourkami-Tutdibi; Dominik Schmitz; Tobias Hüppe (Journal of Medical Case Reports)
Abstract Background This report outlines a case of pseudocholinesterase deficiency in a pediatric patient, whose autosomal recessive condition is caused by two different pathologic variants of the butyrylcholinesterase gene, resulting in a rare case of functional homozygosity. Case presentation A healthy 4-year-old girl of Northern European descent underwent general anesthesia for tonsillotomy, adenoidectomy, and bilateral tympanocentesis. Previously unknown pseudocholinesterase deficiency presented as delayed emergence with sustained apnea and paralysis following administration of mivacurium, necessitating transfer to the pediatric intensive care unit for prolonged post-operative ventilatory support and monitoring. Extubation was safely performed 8 hours later. No long-term sequelae were noted. Genetic testing identified compound heterozygosity in the butyrylcholinesterase gene. Thus, a diagnosis of autosomal recessive hereditary pseudocholinesterase deficiency was made. Conclusion Pseudocholinesterase deficiency will almost always present unexpectedly and must be included in the differential diagnosis of delayed emergence. Once suspected, a clinical diagnosis can be supported using a peripheral nerve stimulator, and confirmed using laboratory tests. Genetic testing can help determine the etiology of disease.